The Transition from Yorùbá Metaphysics to Islamic Aesthetics in Ọláńrewájú Adépọ̀jù’s Poetry - Stephen Toyin Ogundipe (Yoruba Studies Review, 2021)
This paper explores the poetry of Ọlánrewájú Ade ́ ṕ ọ̀jù, a major contemporary Yorùbá poet, based in Ibadan, southwestern Nigeria. Much of the scholarship on the poet focuses purely on his sociopolitical interest, but the development of his craft has been largely ignored. This paper examines peculiar features of Adépọ̀jù’s poetry based on its fusion of Yorùbá cultural and Islamic religious values with the view to theoretically characterizing his practice. It draws on purposefully selected, recorded audio poetic compositions of Adeṕ ọ̀jù produced between 1974 and 2012 in order to yield a comprehensive view of his poetics. It employs hybridity, an aspect of postcolonial theory advanced by Homi Bhabha, as a theoretical framework to analyze the texts. The essay reveals that Adépọ̀jù’s poetry grows from the simple narration of the Yorùba traditional worldview, identity, and ́ òri ̀ṣa pantheon to become an instrument of radical Islamic ideology. It concludes that the integration of the indigenous and the Islamic cultural values in the work of Adeṕ ọ̀jù results in a unique poetic idiom in Yorùbá poetry.